2019
DOI: 10.3389/fpsyg.2019.02071
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Family and Friends on Antisocial Adolescent Behavior: The Mediating Role of Impulsivity and Empathy

Abstract: Adolescence is an especially risky phase for the appearance of antisocial behaviors. Antisocial behavior produces significant individual and social harms, so it is important to provide keys for prevention and treatment. To do that, it is essential to identify the main predictors. The objective of this study is to analyze the effect of family (affection and communication, behavioral control) and friends (antisocial friendships) on adolescent antisocial behavior, as well as the mediating role of adolescent impul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 42 publications
(57 reference statements)
3
19
0
1
Order By: Relevance
“…Research concerning juvenile delinquency and antisocial behaviour has directed particular attention to risk and protective factors [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ], mostly because early intervention is essential and effective in helping reduce punitive measures for children at risk [ 11 ]. The importance of prevention is well-established [ 12 , 13 , 14 ] and elaborating on preventive interventions on the basis of the varied array of risk factors recognized in research literature should be advisable to improve their effectiveness. Understanding the aetiology of offending and violent behaviour is, in fact, believed to be critical in structuring intervention and prevention attempts [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research concerning juvenile delinquency and antisocial behaviour has directed particular attention to risk and protective factors [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ], mostly because early intervention is essential and effective in helping reduce punitive measures for children at risk [ 11 ]. The importance of prevention is well-established [ 12 , 13 , 14 ] and elaborating on preventive interventions on the basis of the varied array of risk factors recognized in research literature should be advisable to improve their effectiveness. Understanding the aetiology of offending and violent behaviour is, in fact, believed to be critical in structuring intervention and prevention attempts [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature on the topic supports the importance of considering the peer group network among the other areas traditionally connected to adolescent antisocial behaviour. Antisocial friendships represent a risk factor for antisocial behaviour in adolescence [ 14 ], and the total level of aggressive behaviour of a single adolescent in the friend network is predictive of the increase in rule-breaking behaviour of that individual over time [ 28 ]. On the other side, adolescent antisocial behaviour itself may represent a means of gaining and maintaining status in the peer group [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, self-esteem and self-concept, both family and academic related, play a protective role, while social self-esteem, on the contrary, plays a risk role (Cava et al, 2008). In opposition to these studies, those who have measured self-esteem as a unitary construct have found that self-esteem plays, in any case, a mediating role (DuBois and Silverthorn, 2004;McKay et al, 2011;Álvarez-García et al, 2019). This means that the effect of certain variables on consumption may not be direct but go through self-esteem.…”
Section: Introductionmentioning
confidence: 97%
“…School is considered to be a context where the adolescent constructs well-being ( Cash et al, 2014 ; Sarkova et al, 2014 ) not only in terms of their academic achievement but also in their relationships with other peers ( Connolly et al, 2015 ; De Boer et al, 2016 ) and in their relationship with their teachers, the climate ( Maxwell et al, 2017 ), the rules for coexistence, the attitudes, and values ( Wang and Eccles, 2012 ; Wang and Fredricks, 2014 ; EMCDDA, 2015 ). Wang and Fredricks (2014) indicated that young people with a low commitment to school showed a higher tendency toward antisocial conducts ( Álvarez-García et al, 2019 ), substance consumption, and early school leaving ( González de Audikana, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, researchers are looking closely at how to mitigate the detrimental effects of negative life events on antisocial behavior tendencies in these adolescents. Antisocial behavior tendencies in adolescence, and its continuation in later life, are believed to involve an interaction of psychological vulnerability and environmental factors (Álvarez-García et al, 2019). Regarding psychological resources, self-esteem is thought to be an important internal resource, which has a significant effect in promoting children's development (Gao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%